Determination of the Factors in Diapause Initiation of White Rice Stem Borer - Teddy Suparno (Universitas Gadjah Mada, 1999)
The objective of this research was to determine the important factors in white rice stem borer larvae, Scirpophaga innotata Walker, entering diapause. The results indicates that white rice stem borer (WRSB) larvae feed on rice plants IR64 grown on soils with continual watering which exposed at short day length (11.76 hours at June 21, 1994) will not be in diapause. However, terminated watering 75 days after transplanting or 15 days after flowering on the host growth media caused diapause. These terminated watering caused declining of soil moisture progressively which had direct effect on rice stem water content, and so affected significantly the increase of abscisic acid (ABA). A changes of primary metabolites (protein, lipid, and methionine) did not cause diapause. The secondary metabolite ABA had juvenile hormone activity in the insects larvae, progressively increased in its content in the rice stem caused the percentage of larval diapause of WRSB to increase. The role of ABA in diapause initiation of WRSB needs more study.